Enhanced critical-size calvarial bone healing by ASCs engineered with Cre/loxP-based hybrid baculovirus. (April 2017) - Lo, Shih-Chun; Li, Kuei-Chang; Chang, Yu-Han; Hsu, Mu-Nung; Sung, Li-Yu; Vu, Truong Anh; Hu, Yu-Chen
Abstract: Calvarial bone repair remains challenging for adults. Although adipose-derived stem cells (ASCs) hold promise to heal bone defects, use of ASCs for critical-size calvarial bone repair is ineffective. Stromal cell-derived factor 1 (SDF-1) is a chemokine capable of triggering stem cell migration. Although recombinant SDF-1 protein is co-delivered with other molecules including BMP-2 to facilitate calvarial bone repair, these approaches did not yield satisfactory healing. This study aimed to exploit a newly developed Cre/loxP-based hybrid baculovirus for efficient gene delivery and prolonged transgene expression in ASCs. We demonstrated that transduction of rat ASCs with the hybrid Cre/loxP-based baculovirus enabled robust and sustained expression of functional BMP-2 and SDF-1. Expression of BMP-2 or SDF-1 alone failed to effectively induce rat ASCs osteogenesis and healing of critical-size calvarial bone defects. Nonetheless, prolonged BMP-2/SDF-1 co-expression in ASCs synergistically activated both Smad and ERK1/2 pathways and hence potentiated the osteogenesis. Consequently, transplantation of the hybrid baculovirus-engineered, BMP-2/SDF-1-expressing ASCs/scaffold constructs potently healed the critical-size (6 mm) calvarial bone defects (filling ≈70% of defect volume), which considerably outperformed the calvarial bone repair using BMP-2/SDF-1 delivered with biomaterial-based scaffolds. These data implicated the potential of Cre/loxP-based hybrid baculovirus vector for ASCs engineering and calvarial bone healing.